Balancing dual roles as mothers and students like a walk on a tight rope? Reflections and experiences of student mothers at a South African higher education institution - Maluleke, U.; Senekal, J.; Munnik, E.; Somhlaba, N. (South African Journal of Higher Education, 2023)
While opportunities for women to study at institutions of higher learning have increased compared to past generations, student mothers, specifically, are confronted with the extra burden of parenting, in combination with their academic work. Using an exploratory design within exploratory research, this study aimed to explore perceptions and experiences of student mothers enrolled at University of the Western Cape. We used a purposive sampling strategy to recruit female student mothers, who had at least one child and were registered for a full-time undergraduate degree at the institution. A total of 25 female students constituted four semi-structured focus groups, with five to seven participants in each. Thematic analysis was used to analyse the data, and Bronfenbrenner’s Process-Person-Context-Time model was adopted, which allowed for a nuanced understanding of the student mother within various contexts. The study received ethics approval and institutional permission from the universities registrar and also adhered to good research ethical principles. Key themes relating to the challenges experienced by student mothers that we identified, included financial difficulties and the stress of balancing their dual responsibilities of being a student and a mother. Proximity to their children complicated their attempt to fulfil dual roles; proximity to the child facilitated a closer bond with the child(ren), but impeded their academic performance. Geographical distance from the child(ren) facilitated their performance as a student, but often at huge emotional expense from participants. Familial support was highlighted as an important facilitator of academic performance. Family members often assisted with care of the child, allowing the student mother to engage in her role as student. Some student mothers perceived a lack of support from the university, while others acknowledged it as their own responsibility to manage their commitments to study. Despite these difficulties, many student mothers found that motherhood was a motivator for them to study, to secure a positive future for themselves and their child(ren).